Chicxulub central zone structure and stratigraphy—PEMEX exploration drilling program - Urrutia-Fucugauchi, Jaime; Pérez-Cruz, Ligia; Wittmann, Axel; Arz, José A.; Arenillas, Ignacio; Xiao, Long; Zhao, Jiawei; Gilabert, Vicente; Salguero-Hernandez, Eduardo (Frontiers in Earth Science, 2025)
The Chicxulub crater was formed by the impact of an asteroid ∼66 Ma ago at the Cretaceous/Paleogene boundary on a carbonate platform in the southern Gulf of Mexico. The impact’s structure is not exposed at the surface, requiring drilling and geophysical surveys to study it. The geophysical and drilling program by Petroleos Mexicanos (PEMEX) provided critical evidence and core samples for petrographic, geochemical and chronostratigraphic studies. The PEMEX boreholes drilled through a sequence of carbonate sediments and igneous-textured rocks, corresponding to the post-impact carbonates and impactite sequence. The Chicxulub-1 (1581.5 m), Sacapuc-1 (1527 m), and Yucatan-6 (1645 m) boreholes reached the impact breccias and melt at ∼1100–1581.5 m, ∼1000–1527 m and 1040/1080–1645 m, respectively. In the Chicxulub-1 and Sacapuc-1 boreholes, post-impact sediments include interbedded marlstones and limestones, and in Yucatan-6, post-impact sediments include limestones, with intercalated layers of marlstones, calcarenites and calcirudists, and a sandy unit between 1040/1080 and 1220/1250 m, interpreted as a carbonate-rich sorted suevite. The impactites are ∼300 m and ∼200 m thick in Sacapuc-1 and Chicxulub-1 boreholes, respectively. Lateral correlations document that the melt sheet/pockets extend across the annular trough and peak ring. Self-potential (SP) logs characterize the carbonate and impactite sections that can be traced across the central zone, with differences in depth and thickness. SP logs record the carbonate and impactite section stratigraphy, with units that can be traced across the central zone. Lithological changes are observed at a depth below ∼900 m in the impactite section. The PEMEX drilling ended within the impactite section, without reaching the target carbonates. The revised borehole columns, logs, micropaleontological reports, and geophysical models provide constraints on post-impact sediments and impactites across the peak ring and annular trough in the central zone.